2016
DOI: 10.3390/ijms17071041
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Aquaporin 1 as a Prognostic Marker in a Prospective Cohort of Malignant Mesotheliomas

Abstract: (1) Background: Malignant mesothelioma (MM) is an aggressive tumour of the serosal membranes, associated with exposure to asbestos. Survival is generally poor, but prognostication for individual patients is difficult. We recently described Aquaporin 1 (AQP1) as independent prognostic factor in two separate retrospective cohorts of MM patients. Here we assess the usefulness of AQP1 prospectively, and determine the inter-observer agreement in assessing AQP1 scores; (2) Methods: A total of 104 consecutive cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Namely, a statistically significant association of AQP‐1 high expression with increased survival was observed with a median OS of 12 months for patients with ≥50% AQP‐1 expression vs a median OS of only 7 months for patients with less than 50% AQP‐1 expression. The relationship between higher levels of AQP‐1 in MM and a better prognosis confirms the results of previous studies, but appears to be in conflict with data reported in other tumours, including breast cancer, melanoma, urothelial carcinoma and pharyngeal squamous cell carcinoma, in which increased levels of AQP1 are associated with a poorer prognosis . These data and the relatively few studies on MM require further validation.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Namely, a statistically significant association of AQP‐1 high expression with increased survival was observed with a median OS of 12 months for patients with ≥50% AQP‐1 expression vs a median OS of only 7 months for patients with less than 50% AQP‐1 expression. The relationship between higher levels of AQP‐1 in MM and a better prognosis confirms the results of previous studies, but appears to be in conflict with data reported in other tumours, including breast cancer, melanoma, urothelial carcinoma and pharyngeal squamous cell carcinoma, in which increased levels of AQP1 are associated with a poorer prognosis . These data and the relatively few studies on MM require further validation.…”
Section: Discussionsupporting
confidence: 55%
“…Cytological and IHC assessments of MM through specific panels of antibodies are available, but prognostic markers are less numerous and not routinely used in MM effusions. Recent studies have reported a potential prognostic significance of AQP‐1 in surgical MM samples . In the current study, we performed an IHC evaluation of AQP1 expression in a cohort of MM patients, living nearby the area of Biancavilla.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important prognostic parameters for MPM include the histological subtype, sex and age at diagnosis [ 4 ]. Recent studies have highlighted the potential role of aquaporin-1 (AQP1) as an independent prognostic factor for improved survival in MPM patients exposed to asbestos [ 5 , 6 ]. AQP1 is a water channel protein found in cell membranes throughout the body and facilitates transcellular water transport [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is potentially significant in MM, which commonly presents with large pleural effusions, which interfere with breathing and thus contribute to poor quality of life. Retained expression of AQP1 by immunohistochemistry in MM histology specimens has been associated with better overall survival, indicating a potential role in pathogenesis [ 23 , 24 ]. Furthermore, increased AQP1 protein and mRNA expression have been observed in epithelioid MM subtypes, which have a better prognosis when compared to biphasic and sarcomatoid subtypes [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%